Potential of Butterfly Pea Cream (Clitoria ternatea) in Skin Regeneration by Increasing the Number of Fibroblasts and Collagen Thickness - Rizki Noval Nursyafillah; Buwono Puruhito; Liza Afriliana; Hermawan Istiadi; Galih Sari Damayanti (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Indonesia is a tropical country that has a high exposure to UV radiation that causes. To overcome these effects, antioxidants are needed that can inhibit the effects of UV radiation. Clitoria ternatea, which is rich in flavonoids, is able to fight free radicals and reduce the effects of photoaging. Objective: This study aims to determine the effect of Clitoria ternatea extract cream on the number of fibroblasts and collagen thickness in UVB-induced male white rats. Methods: This study was a true experimental type with a post-test only control group design with 36 male White rats divided into 4 groups. Clitoria ternatea extract cream was administered in 3 levels (2.5%, 5%, 10%) and Synchro® placebo base cream was applied on the rats' back for 30 days. Irradiation was performed 3 times a week, and the cream was applied twice a day. Statistical analysis was performed to see the mean differences between groups in UVB-induced male white rats. Results: The application of Clitoria ternatea extract cream with levels of 2.5%, 5%, and 10% can increase the number of fibroblasts significantly (p<0.05) from 7.40 ± 0.81 to 9.40 ± 1.39; 11.33 ± 1.73; 12.00 ± 1.49. At 5% and 10% levels can increase collagen thickness significantly (p<0.05) from 64.44 ± 5.64 to 70.75 ± 4.44; 77.43 ± 4.27. Conclusion: It can be concluded that Clitoria ternatea extract cream 2.5%, 5% and 10% can increase the number of fibroblasts and Clitoria ternatea extract cream 5% and 10% can increase collagen thickness. Keywords:  Clitoria ternatea; Collagen; Fibroblast; Flavonoid; Photoaging; UVB.